Answer:
The equation for area of a triangle is height multiplied by the base length, divided by 2. So, if the height is 2, and the base is 4, then you multiply the two together, making 8, and then divide it by 2, making the final area 4. So if the dimensions are doubled, then the equation would be 4 times 8 divided by 2. Which is 16. If we do this again with 16 times 8, we will get 128, which when divided by two is 64. This is 4 times 16, just as 16 is 4 times the original answer 4. This means that every time you double the dimensions you will get the original answer multiplied by 4.
Step-by-step explanation:
Answer:
- The center (2, 2.5), radius
/ 2
Step-by-step explanation:
<u>The standard form of the equation of a circle is: </u>
- ( x - h )^2 + ( y - k )^2 = r^2, where ( h, k ) is the center and r is the radius
<u>Rewrite the given equation in the standard form:</u>
- 2x^2 + 2y^2 - 8x + 10y + 2 = 0
- x^2 - 4x + y^2 + 5y = -1
- x^2 - 4x + 2^2 + y^2 + 5y + (5/2)^2 = -1 + 4 + 25/4
- (x - 2)^2 + (y + 2.5)^2 = 37/4
<u>The center is:</u>
<u>And radius is:</u>
- <u />
/ 2
There is no difficulty in this problem until you construct the figures. How can we do it is shown in the attached picture. After drawing PRST, from the point P, we can draw PMKD and later we can complete PMCT as a result. From this picture, we can see that the side of PMCT is also a. Then, the area of this square is
Answer:
y=2x-1
Step-by-step explanation:
Answer:
Option C (1, 0)
Step-by-step explanation:
We have a system with the following equations:
![y = x ^ 2-1\\\\y = 2x-2](https://tex.z-dn.net/?f=y%20%3D%20x%20%5E%202-1%5C%5C%5C%5Cy%20%3D%202x-2)
The first equation is a parabola.
The second equation is a straight line
To solve the system, substitute the second equation in the first and solve for x.
![2x-2 = x ^ 2 -1](https://tex.z-dn.net/?f=2x-2%20%3D%20x%20%5E%202%20-1)
Simplify
![x ^ 2-2x + 1 = 0](https://tex.z-dn.net/?f=x%20%5E%202-2x%20%2B%201%20%3D%200)
You must search for two numbers that when you add them, obtain as a result -2 and multiplying both results in 1.
These numbers are -1 and -1
Therefore
![x ^ 2-2x + 1= (x-1)(x-1)\\\\x ^ 2-2x + 1= (x-1)^2=0](https://tex.z-dn.net/?f=x%20%5E%202-2x%20%2B%201%3D%20%28x-1%29%28x-1%29%5C%5C%5C%5Cx%20%5E%202-2x%20%2B%201%3D%20%28x-1%29%5E2%3D0)
Finally the solutions are
![x = 1\\y =0](https://tex.z-dn.net/?f=x%20%3D%201%5C%5Cy%20%3D0)